IDENTITAS DAN MARJINALISASI: ORANG KUBU, ORANG RIMBA, SUKU ANAK DALAM (Universitas Kristen Satya Wacana, 2022)
This article, through the available literature, explores and problematising the shifting social and cultural identity of a minority ethnic group resided in the Province of Jambi, Sumtara; that at least has three names: Orang Kubu, Orang Rimba and Suku Anak Dalam (SAD). Frrom the changes of their names reveal the pattern of power relation that is historically embedded within their interaction with the major etnic groups and the state. In such an asymetric power relationship contexts researchers, academicians, social activists and state apparatuses; play their important roles as interlocutors and establishes the usage of names according to their own interests. As a minority ethnic group their livelihood which is closely related with tropical forrest environment in Bukit Dua-Belas; have rapidly change as it converse into transmigration areas and palm oil plantations. The weak postion in relation to the dominant ethnic groups and the state, the proses of marginalisastion occured in the interaction. The prospek of this vunarable ethnic minority group is bleak and their future only be saved through the proper affirmation action from the state.